2018
DOI: 10.1002/smll.201803564
|View full text |Cite
|
Sign up to set email alerts
|

Core–Shell Hybrid Nanowires with Protein Enabling Fast Ion Conduction for High‐Performance Composite Polymer Electrolytes

Abstract: Incorporating nanofillers is one of the promising approaches for simultaneously boosting the ionic conductivity and mechanical properties of solid polymer electrolytes (SPEs). However, effectively creating faster ion‐conduction pathways via nanofillers still remains a big challenge. Herein, core–shell protein–ceramic nanowires for more efficiently building fast ion‐conduction networks in SPEs are reported. The core–shell protein–ceramic nanowires are fabricated via in situ growth of protein coating on the elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…The inconsistence between the ion‐transport resistance and air‐flow resistance of zein/CNF and PVP/CNF arises from the unique surface properties of zein. As zein possesses abundant functional groups, which may show unique interactions with ions thus helping the ion‐transport . The optimal porous structure and low ion‐transport resistance of gelatin/CNF interlayer will significantly benefit the battery performance especially the rate capability.…”
Section: Resultsmentioning
confidence: 99%
“…The inconsistence between the ion‐transport resistance and air‐flow resistance of zein/CNF and PVP/CNF arises from the unique surface properties of zein. As zein possesses abundant functional groups, which may show unique interactions with ions thus helping the ion‐transport . The optimal porous structure and low ion‐transport resistance of gelatin/CNF interlayer will significantly benefit the battery performance especially the rate capability.…”
Section: Resultsmentioning
confidence: 99%
“…reported unique core-shell protein@TiO 2 nanowires (NWs) towards high-performance composite polymer electrolytes with faster ion-conduction pathways. [46] It is demonstrated that composite electrolytes with these NWs effectively resulted in superiorp roperties, including faster ion conduction, stronger mechanical properties, better electrochemical stability,a nd even higher Li + transference number.I mportantly,m echanistic analysisindicates that the protein plays acrucial role in dissociating Li salts and conducting Li + ,w hich are beneficial for facilitating faster ion conduction at the interface of polymer-NWs because of strongi nteractions between the protein and ions (Figure 4).…”
Section: Organic-inorganic Inert Ceramic Csesmentioning
confidence: 99%
“…In 1988, Skaarup et al first constructed am ixed-phase composite electrolyte consisting of PEO polymer matrix and ionconducting Li 3 N. [61] The room-temperature ionic conductivity is improved with an increase in Li 3 Na nd reaches am aximum value with small volumepercentages of polymer (5-10 %). Sub- [46] sequently,Z hang et al reported ac omposite electrolyte containing ion-conductive (LiAlTiP) x O y glass and PEO matrix. [62] The composite electrolyte shows an improved room-temperature conductivity of 1.7 10 À4 Scm À1 and Li transfer number of 0.39 with optimized composition.…”
Section: Oxide Ionic Conductorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Core–shell hybrid nanowires (NWs) for polymer electrolyte (Reproduced with permission. [ 142 ] Copyright 2018, Wiley‐VCH): h) The advantages of protein@TiO 2 NWs over protein–TiO 2 NPs for building faster ion‐conduction pathways in SPEs.…”
Section: Proteins As Components Of Rechargeable Batteriesmentioning
confidence: 99%